The utilization of cultural lexicon in creative industry products: A maintenance strategy of Yogyakartan Javanese language - Putra, Dona Aji Karunia; Muttaqien, Muhammad Zainal (Universitas Dian Nuswantoro, 2024)
Creative industries can contribute to the economic growth of local communities while promoting and preserving local languages and culture. Based on these basic assumptions, this research was conducted to describe the forms and functions of Javanese language and culture used in creative industry products and the factors behind the use of regional language and culture in creative industries. This research used a qualitative descriptive method with a sociolinguistic and creative industry perspective. The research was conducted in three local government areas in Yogyakarta. Data collection was carried out through documentation, document analyses, and interviews. The data covers various aspects of the Javanese language and culture, such as words, phrases, clauses, sentences, proverbs, Javanese script, naming and greeting systems, and proverbs. The results show that various creative industry products incorporate the Yogyakartan Javanese cultural and linguistic lexicon in their product branding, packaging, and design content. The cultural lexicon consists of Javanese writing, art, traditional clothing, drinks, greetings, phatic forms, and proverbs. Utilizing the Javanese language and cultural lexicon in creative industries can be an effective marketing strategy and an innovative step in preserving and developing local cultural heritage. This can significantly contribute to local economic growth, increase awareness of cultural diversity, and strengthen the community's cultural identity.